Stability of anchored retaining walls under seismic loading conditions to obtain minimal anchor lengths using the improved failure model - Benamara, Fatima Zohra; Rouaiguia, Ammar; Bencheikh, Messaouda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Anchored retaining walls are structures designed to support different loading applied in static and dynamic cases. The purpose of this work is to design and study the stability of an anchored retaining wall loaded with different seismic actions to obtain minimal anchor lengths. Mononobe-Okabe theory has been applied for the evaluation of seismic earth pressures developed behind the anchored wall.
Keywords: anchored retaining walls; safety factor; stability; seismic loading; failure model; Plaxis 2D; kotwione ściany oporowe; współczynnik bezpieczeństwa; stabilność; obciążenie sejsmiczne